Human iPSC‐Derived Neural Progenitors Preserve Vision in an AMD‐Like Model. (2nd June 2015) - Tsai, Yuchun; Lu, Bin; Bakondi, Benjamin; Girman, Sergey; Sahabian, Anais; Sareen, Dhruv; Svendsen, Clive N.; Wang, Shaomei
Abstract Pluripotent stem cell‐derived retinal pigment epithelial (RPE) cells are currently being tested for cell replacement in late‐stage age‐related macular degeneration (AMD). However, preserving vision at early‐stages may also be possible. Here, we demonstrate that transplantation of neural progenitor cells (NPCs) derived from induced pluripotent stem cells (iNPCs) limits disease progression in the Royal College of Surgeons rat, a preclinical model of AMD. Grafted‐iNPCs survived, remained undifferentiated, and distributed extensively in a laminar fashion in the subretinal space. Retinal pathology resulting from the accumulation of undigested photoreceptor outer segments (POS) was significantly reduced in iNPC‐injected rats compared with controls. Phagosomes within grafted‐iNPCs contained POS, suggesting that iNPCs had compensated for defective POS phagocytosis by host‐RPE. The iNPC‐treated eyes contained six to eight rows of photoreceptor nuclei that spanned up to 5 mm in length in transverse retinal sections, compared with only one row of photoreceptors in controls. iNPC treatment fully preserved visual acuity measured by optokinetic response. Electrophysiological recordings revealed that retina with the best iNPC‐protected areas were 140‐fold more sensitive to light stimulation than equivalent areas of contralateral eyes. The results described here support the therapeutic utility of iNPCs as autologous grafts for early‐stage of AMD. Stem Cells2015;33:2537–2549